Non-coding RNA in bladder cancer - Li, Yi; Li, Gang; Guo, Xiangyang; Yao, Haochen; Wang, Guoqing; Li, Chong (Cancer letters, 2020)
Bladder cancer is the tenth most common cancer worldwide and has been associated with high mortality and morbidity. Although the treatment of bladder cancer is based on well-defined tumor classifications and gradings, patients still experience different clinical response. The heterogeneity of this disease calls for substantial research with more in-depth molecular characterization, with the hope of identifying new diagnostic and treatment options. In recent years, non-coding RNAs (ncRNAs), particularly, microRNAs (miRNAs), long non-coding RNA (lncRNAs), and circular RNAs (circRNAs) were found to be associated with bladder cancer occurrence and development. This review highlights the recent findings concerning ncRNAs and their relevance to the pathogenesis of bladder cancer. This may provide a foundation for developing highly specific diagnostic tools and more robust therapeutic strategies in the future.